Quality of Life Assessment after Pancreatic Enzyme Replacement Therapy in Chronic Pancreatitis - László Czakó; Tamás Takács; Peter Hegyi; László Prónai; Zsolt Tulassay; Lilla Lakner; Zoltán Döbrönte; Krisztina Boda; János Lonovics (Canadian Journal of Gastroenterology)
GOALS: To evaluate the quality of life (QoL) of patients with chronic pancreatitis before and after pancreatic enzyme replacement therapy in a prospective, multicentre, follow-up study.